Firm Location and the Determinants of Exporting in Developing Countries - Farole, Thomas; Winkler, Deborah (2012)
Using a cross-section of more than 40,000 manufacturing and services firms in 79 developing countries from the World Bank's Enterprise Surveys Database, this paper assesses how firm location determines the likelihood and extent of exporting in developing countries. Descriptive statistics confirm higher export participation (but not intensity) for firms in core versus non-core regions, despite the finding that firms in the core assess many aspects of the investment climate more negatively. Results from a probit model show that, in addition to firm-specific characteristics, both regional investment climate and agglomeration factors have a significant impact on export participation. Specifically, customs clearance and electricity quality matter for export participation for manufacturing firms. Although localization economies and export spillovers are associated with increased exporting, the opposite is found for urbanization economies for both manufacturing and services firms. The analysis finds that firm-level determinants of exporting matter more for firms located in non-core regions, while regional determinants and agglomeration economies play a larger role in core regions. The findings point to the presence of congestion costs in the core, and suggest that policy interventions to target export participation are likely to have a greater impact if they are focused on core regions over non-core regions, where firm-specific factors predominate. Moreover, the importance of export spillovers and localization economies highlights the potential value of efforts to remove barriers to natural agglomeration both in core and non-core regions, for example through investments in infrastructure, the provision of social services, and regional integration arrangements.